2020
DOI: 10.1175/jcli-d-19-0833.1
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Decline and Recovery of Indian Summer Monsoon Rainfall: Relative Roles of External Forcing and Internal Variability

Abstract: The Indian summer monsoon (ISM) rainfall affects a large population in South Asia. Observations show a decline in ISM rainfall from 1950 to 1999 and a recovery from 1999 to 2013. While the decline has been attributed to global warming, aerosol effects, deforestation, and a negative-to-positive phase transition of the interdecadal Pacific oscillation (IPO), the cause for the recovery remains largely unclear. Through analyses of a 57-member perturbed-parameter ensemble of model simulations, this study shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 72 publications
1
40
0
Order By: Relevance
“…2d ). We find that the composite differences resemble the IPO-like pattern in both observation 39 and the internal IPO mode of MPI-GE (Supplementary Fig. 1a ), implying that IPO is the dominant internal mode in regulating the PWC variabilities.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…2d ). We find that the composite differences resemble the IPO-like pattern in both observation 39 and the internal IPO mode of MPI-GE (Supplementary Fig. 1a ), implying that IPO is the dominant internal mode in regulating the PWC variabilities.…”
Section: Resultsmentioning
confidence: 64%
“…By adding an adjustment term to the original PWC trend following refs. 39 , 56 , the adjusted linear trend of the PWC is given by where the adjusted PWC trend of member [ ] is the sum of the forced PWC trend [ ] plus the internal component of the PWC trend [ ] with an adjustment term [ ]. The internal adjusted PWC trend is expressed as where where is the adjustment term and takes the observed IPO phase transitions into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…The Indian summer monsoon exhibits strong interannual variability from bi-annual to multi-decadal time scales 1 5 . These variations are due to external forcings as well as internal variability of the non-linear system 6 , 7 . Tropical teleconnections such as the El Nino Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the tropical Atlantic variability (ATL), and the preceding winter ENSO (W-ENSO) influences ISM rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of global monsoon are modulated by several factors. Different factors including the greenhouse gases (GHGs) (Kitoh et al, 2013;Song et al, 2014;Chen and Zhou, 2015), anthropogenic aerosols (AAs) (Held et al, 2005;Lau et al, 2006;Meehl et al, 2008;Bollasina et al, 2011;Qian et al, 2011;Jiang et al, 2013Jiang et al, , 2015Guo et al, 2013;Wu et al, 2013;Polson et al, 2014;Song et al, 2014;Li et al, 2016;Zhang et al, 2018), and natural internal variability of the climate system, such as the Inter-decadal Pacific Oscillation (IPO) (Zhu and Yang, 2003;Yang et al, 2004;Zhou et al, 2008b;Li et al, 2010;Wang et al, 2012;Huang et al, 2020), have been proposed to explain the observed reduction in monsoon precipitation. The impact of individual factors is regional dependent, including the sign and magnitude of impact (Polson et al, 2014;Pascale et al, 2017).…”
Section: Introductionmentioning
confidence: 99%